Diagnostic exome sequencing of syndromic epilepsy patients in clinical practice. Issue 5 (23rd March 2018) - Tumienė, B.; Maver, A.; Writzl, K.; Hodžić, A.; Čuturilo, G.; Kuzmanić‐Šamija, R.; Čulić, V.; Peterlin, B.
Abstract : Although genetic revolution of recent years has vastly expanded a list of genes implicated in epilepsies, complex architecture of epilepsy genetics is still largely unknown, consequently, universally accepted workflows for epilepsy genetic testing in a clinical practice are missing. We present a comprehensive NGS‐based diagnostic approach addressing both the clinical and genetic heterogeneity of disorders involving epilepsy or seizures. A bioinformatic panel of 862 epilepsy‐ or seizure‐associated genes was applied to Mendeliome (4813 genes) or whole‐exome sequencing data as a first stage, while the second stage included untargeted variant interpretation. Eighty‐six consecutive patients with epilepsy or seizures associated with neurodevelopmental disorders and/or congenital malformations were investigated. Of the 86 probands, 42 harbored pathogenic and likely pathogenic variants, giving a diagnostic yield of 49%. Two patients were diagnosed with pathogenic copy number variations and 2 had causative mitochondrial DNA variants. Eleven patients (13%) were diagnosed with diseases with specific treatments. Besides, genomic approach in diagnostics had multiple additional benefits due to mostly non‐specific, overlapping, not full‐blown phenotypes and abilities to diagnose novel and ultra rare epilepsy‐associated diseases. Likely pathogenic variants were identified in SOX5 gene, not previously associated with epilepsy, and UBA5, a recently associated with epilepsy gene. Abstract :